2015
DOI: 10.1088/0004-637x/806/1/55
|View full text |Cite
|
Sign up to set email alerts
|

A Steady-State Picture of Solar Wind Acceleration and Charge State Composition Derived From a Global Wave-Driven MHD Model

Abstract: The higher charge states found in slow (<400km s −1 ) solar wind streams compared to fast streams have supported the hypothesis that the slow wind originates in closed coronal loops, and released intermittently through reconnection. Here we examine whether a highly ionized slow wind can also form along steady and open magnetic field lines. We model the steady-state solar atmosphere using AWSoM, a global magnetohydrodynamic model driven by Alfvén waves, and apply an ionization code to calculate the charge state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 103 publications
0
38
0
Order By: Relevance
“…used the models of Hansteen and Leer (1995), Cranmer, van Ballegooijen, and Edgar (2007), and Oran et al (2013) to predict the intensities of emission lines and the fast solar wind charge state distributions, and found that while transitionregion lines are predicted well, coronal line intensities and the fast wind charge state distribution are underpredicted, possibly due to the fast wind encountering difficulties to reach the high ionization stages corresponding to local conditions. Oran et al (2015) calculated the charge state evolution covering all latitudes in a realistic open magnetic field, and obtained similar results. In particular, the O viii / O vii and C vii / C vi charge state ratios are underpredicted when compared to Ulysses observations.…”
Section: Non-equilibrium Ionization and Solar Windmentioning
confidence: 73%
See 1 more Smart Citation
“…used the models of Hansteen and Leer (1995), Cranmer, van Ballegooijen, and Edgar (2007), and Oran et al (2013) to predict the intensities of emission lines and the fast solar wind charge state distributions, and found that while transitionregion lines are predicted well, coronal line intensities and the fast wind charge state distribution are underpredicted, possibly due to the fast wind encountering difficulties to reach the high ionization stages corresponding to local conditions. Oran et al (2015) calculated the charge state evolution covering all latitudes in a realistic open magnetic field, and obtained similar results. In particular, the O viii / O vii and C vii / C vi charge state ratios are underpredicted when compared to Ulysses observations.…”
Section: Non-equilibrium Ionization and Solar Windmentioning
confidence: 73%
“…It is possible to do this with a variety of models including different Poynting flux values or magnetic field geometries (open or closed) in different regions such as coronal holes, and even eruptions constituting transients in the solar wind (e.g., Lynch et al, 2011;Gruesbeck et al, 2011;Landi et al, 2012aLandi et al, ,b, 2014Lepri et al, 2012;Oran et al, 2015;Rodkin et al, 2016).…”
Section: Non-equilibrium Ionization and Solar Windmentioning
confidence: 99%
“…This very difficulty makes the reproduction of charge-states in MHD computational models of the solar corona a robust constraint for the validation of the models themselves. Oran et al (2015) pioneered in this effort by using an external code to evaluate charge states in the solar wind calculation obtained with the Alfvén Wave Solar Model (AWSoM), and comparing them with in situ measurements from Ulysses. Recently we incorporated a Wave-Turbulence-Driven (WTD) formulation for coronal heating and solar wind acceleration by Alfvénic turbulence into a 3D MHD model of the global solar corona (Mikić et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Parker (1958) originally posited that stellar winds must exist due to the thermodynamic pressure gradient between the high temperature corona and interplanetary space. Continued solar observations have constrained theoretical models for the solar wind to a high degree of accuracy (van der Holst et al 2014;Usmanov et al 2014;Oran et al 2015). Recent models of the solar wind are beginning to accurately reproduce the energetics within the corona and explain the steady outflow of plasma into the Heliosphere (e.g.…”
Section: Introductionmentioning
confidence: 99%